Localized Pulmonary Vein Scar Promotes Atrial Fibrillation in High Left Atrial Pressure - Gottlieb, Lisa A.; Vaillant, Fanny; Abell, Emma; Belterman, Charly; Loyer, Virginie; El Hamrani, Dounia; Naulin, Jérôme; Constantin, Marion; Quesson, Bruno; Boukens, Bastiaan J.; Coronel, Ruben; Dekker, Lukas R. C. (Frontiers in Physiology, 2021)
Background: Pulmonary vein (PV) ablation is unsuccessful in atrial fibrillation (AF) patients with high left atrial (LA) pressure. Increased atrial stretch by increased pressure is proarrhythmic for AF, and myocardial scar alters wall deformation. We hypothesized that localized PV scar can be proarrhythmic for AF in high LA pressure. Methods: Radiofrequency energy was delivered locally in the right PV of healthy sheep. The sheep recovered for 4 months. Explanted hearts (n=9 PV scar, n=9 controls) were perfused with 1:4 blood:Tyrode’s solution in a four-chamber working-heart set-up. Programmed PV stimulation was performed during low (~12mmHg) and high (~25mmHg) LA pressure. An AF inducibility index was calculated based on number of induction attempts and number of attempts causing AF (run of ≥20 premature atrial complexes). Results: In high LA pressure, the presence of PV scar increased the AF inducibility index compared to control hearts (0.83±0.20 vs. 0.38±0.40 arb. unit, respectively, p=0.014). The diastolic stimulation threshold in high LA pressure was higher (108±23 vs. 77±16 mA, respectively, p=0.006), and its heterogeneity was increased in hearts with PV scar compared to controls. In high LA pressure, the refractory period was shorter in PV scar than control hearts (178±39 vs. 235±48 ms, p=0.011). Conclusion: Localized PV scar only in combination with increased LA pressure facilitated the inducibility of AF. This was associated with changes in tissue excitability remote from the PV scar. Localized PV ablation is potentially proarrhythmic in patients with increased LA pressure.